KEPEMIMPINAN INKLUSIF: STRATEGI RESPONSIF GENDER DALAM PENDIDIKAN ISLAM DENGAN PENDEKATAN FIQH AL-HADIS - Dewi Ratnawati; Muhammad Anshori; Dika Tripitasari (Jurnal Manajemen Pendidikan, 2026)
The purpose of this research is to create an inclusive educational environment as mentioned in the Hadith and the Word of God, protecting and supporting the realization of the rights of every individual within an educational institution, eliminating claims (of institutions belonging to one group), and ensuring the freedom to enjoy educational facilities without discrimination based on background. The reason for this research is that inclusive leadership in Islamic-based educational institutions has not been optimally implemented. This is evidenced by several previous studies that have addressed some of these issues, but they cannot yet be categorized as alternative solutions for creating inclusive educational leadership, especially in Islamic-based educational institutions. The previous research reviewed focuses on universal inclusive leadership and women's leadership from the perspective of the Hadith and the Quran. This research uses a qualitative approach with literature-based methods based on the texts of the Prophet's Hadith and the Quran. The research results are divided into three aspects. First, the principle of naqli evidence as the basis for strategies, including equality in creation, equality in self-development (seeking knowledge, and equality of rights and obligations/justice). Second, the inclusive leadership strategy includes establishing an anti-discriminatory environment and decision-making through holistic deliberation. Third, gender-based curriculum revitalization includes the reconstruction of biased texts and the strengthening of women's roles.